Embodying the divine in Bali gender, ritual authority, and the politics of representation in Hindu - Jero, Ni Wayan Jemiwi; Jha, Gautam Kumar; Kashiwa, Miki; Paul, Sanghati (Dharmakirti : International Journal of Religion, Mind and Science, 2025)
Background: This article examines how women's bodies serve as a medium for divine power, or Śakti (transcendent feminine power), in Balinese Hindu rituals, to explain the articulation of religious authority and gender representation within patriarchal customary structures. Conceptually, this study draws on literature concerning ritual embodiment, religion as material practice, and community-based gender activism, which shows that religious authority arises from the performativity of sanctity embedded in social relations. Methods: The methods used include religious ethnography with participant observation, semi-structured interviews, and the documentation of rituals performed by female leaders such as Jero Mangku Istri and Jero Balian, as well as an in-depth case study of a female priest who her community has recognized since childhood as a medium for the goddess Danu. Finding: Women are not merely ritual performers but key actors who materialize and mediate the divine through movement, voice, and spiritual service; their authority is often not formally institutionalized but gains spiritual and symbolic legitimacy through communal recognition. These results align with the framework of ritual and material religion: transcendent experiences, the performativity of sanctity, and social networks work together to shape women's religious authority despite structural male domination. Conclusion: In conclusion, women's bodies become a field of negotiation between the sacred and the profane as well as a source of effective religious authority at the practical level. Novelty/Originality of this article: The novelty of this research lies in its empirical demonstration of how women's bodies as mediums of Śakti generate community-recognized authority despite not being formalized, as well as in its integration of religious ethnography with the framework of materialization and religion to map the dynamics of gender and power in contemporary Balinese Hinduism.